Automated multi‐attribute method sample preparation using high‐throughput buffer exchange tips. (10th December 2021) - Ogata, Yuko; Quizon, Pamela M.; Nightlinger, Nancy S.; Sitasuwan, Pongkwan; Snodgrass, Casey; Lee, L. Andrew; Meyer, Jeffrey D.; Rogers, Richard S.
Abstract : Rationale: The multi‐attribute method (MAM) has become a valuable mass spectrometry (MS)‐based tool that can identify and quantify the site‐specific product attributes and purity information for biotherapeutics such as monoclonal antibodies (mAbs) and fusion molecules in recent years. As we expand the use of the MAM at various stages of drug development, it is critical to enhance the sample preparation throughput without additional chemical modifications and variability. Methods: In this study, a fully automated MAM sample preparation protocol is presented, where rapid desalting in less than 15 minutes is achieved using miniaturized size‐exclusion chromatography columns in pipette tips on an automated liquid handler. The peptide samples were analyzed using an electrospray ionization (ESI) orbitrap mass spectrometer coupled to an ultra‐high‐performance liquid chromatography (UHPLC) system with a dual column switching system. Results: No significant change was observed in product attributes and their quantities compared with manual, low‐artifact sample preparation. The sample recovery using the buffer exchange tips was greatly enhanced over the manual spin cartridges while still demonstrating excellent reproducibility for a wide variety of starting sample concentrations. Unlike a plate desalting system, the individual columns provide flexibility in the number of samples prepared at a time and sample locations within plates. Conclusions: This automated protocol enables the preparation of up to 96 samples with less "at‐bench" time than the manual preparation of a smaller batch of samples, thereby greatly facilitating support of process development and the use of the MAM in quality control.